ʻAnusō̜n nư̄ang nai ngān phrarātchathān phlœ̄ng sop Khun Čhamnong Phiromphakdī Pō̜.Phō̜., Thō̜.Čhō̜., Phō̜.Pō̜.Rō̜.4 na mēn lūang nā Phlapphlā ʻItsariyāphō̜n, Wat Thēpsirinthrāwāt, Krung Thēp Mahā Nakhō̜n, wanthī 3 Mēsāyon 2559 - Čhamnong Phiromphakdī (Khrō̜pkhrūa Phiromphakdī, 2016)
Life and works of Chamnong Phiromphakdī, 1928-2015, a former Thai businessman; volume brought out for the crematee's funeral
Cremation volume for Čhamnong Phiromphakdī, จำนงค์ ภิรมย์ภักดี, Nangsư̄ ‘Anusō̜n ngānsop
Keywords: Biografie; Katalog; Festschrift; Businesspeople; Clocks and watches; Cremation Volume